Analisis Pengaruh Sistem Pembayaran Non Tunai Terhadap Pertumbuhan Ekonomi Indonesia Dengan Inflasi Sebagai Variabel Intervening Dalam Perspektif Ekonomi Islam - Purba, Hana Ayunda; Harahap, Isnaini; Atika, Atika (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Indonesia's economic growth has decreased over the past 10 years starting from 2010 to 2021The decline in economic growth declined sharply in 2020 marked by the emergence of the rapid spread of the COVID-19 outbreak in Indonesia which had a major impact on the Indonesian economy. According to Islamic economic studies, economic growth is not only measured by the volume of goods and services produced in a certain period. But also continuous changes in religious, social and community aspects. This study aims to obtain empirical evidence of the effect of non-cash payment systems (number of ATM/debit card transactions and number of credit card transactions on the dependent variable, namely economic growth through inflation as an intervening variable. The type of data used in this study is secondary data in the form of time data monthly series with the period from 2016 to 2021 published by Bank Indonesia and the Central Statistics Agency through the official website.The data analysis technique uses a path analysis model.The results show that directly the number of ATM/Debit card transactions (X1) and the number credit card transactions (X2) have a positive and significant effect on economic growth (Y) and inflation (Z) Indirectly inflation (Z) has a positive and significant effect on economic growth (Y) Indirectly, based on inflation Sobel test calculations (Z) unable to mediate the relationship between the effect of volume tr ATM/debit card transactions (X1) and credit card transaction volume (X2) on economic growth.